Efficacy of oral retinoids for keratoacanthoma centrifugum marginatum. Issue 3 (14th March 2020) - Mizuta, Haruki; Takahashi, Akira; Mori, Taisuke; Namikawa, Kenjiro; Nakano, Eiji; Muto, Yusuke; Jinnai, Shunichi; Nakama, Kenta; Tsutsui, Keita; Yamazaki, Naoya
Abstract: Keratoacanthoma centrifugum marginatum (KCM) is a rare variant of keratoacanthoma. This condition is difficult to diagnose because of its large size and expansive nature and may be diagnosed as a malignant tumor. There are various treatments such as surgery and oral retinoids; however, limited studies have verified their effectiveness. Here, we report a case of KCM on the anterior chest of a 50‐year‐old woman and evaluate the efficacy of oral retinoids. In this case, oral retinoids were highly effective for KCM treatment. A total of 55 cases of KCM, including 54 previously reported cases, were reviewed, and their clinical characteristics and treatment were examined. In this report, 14 of 16 patients were effectively treated with oral retinoids, resulting in a treatment rate of 87.5%. Furthermore, even low‐to‐medium doses were sufficient for treatment and prevention. KCM can be misdiagnosed as a malignant disease based on its clinical features. Due to its large size and expansive nature, a wide excision may be performed; however, because oral retinoids have a very high response rate, an accurate diagnosis will help avoid an unnecessary wide excision.